Cost efficiency analysis of scheduled commercial banks: empirical evidence from India. Issue 7 (13th August 2018) - Bhatia, Aparna; Mahendru, Megha
Abstract : Purpose: The purpose of this paper is to analyze and evaluate cost efficiency (CE) scores of Indian Scheduled Commercial Banks (SCBs) in India over a period of 22 years, i.e. 1991–1992 to 2012–2013. Design/methodology/approach: Data envelopment analysis (DEA) – a non-parametric approach is used to calculate efficiency scores of banks. Further the efficiency scores are decomposed into technical and allocative efficiency. The differences in the efficiency scores across ownership as well as across reformatory and post-reformatory era are examined by applying Panel Tobit Regression. Findings: The paper also identifies the reason for cost inefficiency among Indian banks. In addition, the nature of their return to scale of all SCBs has also been evaluated. The results of the paper depict that Indian SCBs have never achieved full CE score of 1 in any of the years of study. The dominant reason identified behind cost inefficiency is allocative inefficiency. Surprisingly, the results also highlight that SCBs exhibit higher CE scores in reformatory era as compared to the post-reformatory era. Originality/value: With specific reference to India, even lesser literature is found on CE. Indian banking sector has witnessed many changes on account of liberalization, privatization and globalization (LPG). Before banks adapted to the new environment, the global financial crisis acted as a fuel to fire affecting the performance of banks. Thus, a reassessment over a longer period would help to know a wholistic view of the issue of cost inefficiency, which has always been a troubling factor for Indian banks.